Analisis Kebutuhan Mahasiswa terhadap Pengembangan Bahan Ajar pada Mata Kuliah Evaluasi Proses dan Hasil Pembelajaran Biologi - Ratih Komala Dewi (Eduscience Development Journal, 2022)
This research was motivated by insufficient teaching materials and did not fully support the learning process in the Biology learning process and outcome evaluation course. The purpose of this study was to analyze student needs for teaching materials in the Biology learning process and outcome evaluation course. This type of research is descriptive research through the distribution of questionnaires. The sample in this study amounted to 16 students. The research data was obtained from the results of the analysis of questionnaires filled out by students. The results of the study indicate that students need teaching materials to support the learning process.